2019
DOI: 10.1039/c9ta09975a
|View full text |Cite
|
Sign up to set email alerts
|

Ambient fast, large-scale synthesis of entropy-stabilized metal–organic framework nanosheets for electrocatalytic oxygen evolution

Abstract: A high entropy metal–organic framework (HE-MOF) with five near-equimolar components was synthesized by a solution phase method and served as an electrochemical oxygen evolution catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
83
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(83 citation statements)
references
References 37 publications
0
83
0
Order By: Relevance
“…It was found that various factors including the feed ratio of the reactant components, preparation process, condition control, and characterization method have been found to be significantly regulated the morphologies and electronic structures of the resulting electrocatalysts. In particular, the cooperated effects from different components, such as mixed metallic species, structurally related organic ligand as well as the nanomaterials and the substrate, can greatly improve the electrocatalytic performances by modulating the morphological and electronic structures, which then further enhance the electrocatalytic activity and durability through the optimized absorption energy towards the active species . For example, a bimetallic MOF with mixed terephthalate and 2‐aminoterephthalate ligands directly immobilizated on the NF has exhibited enhanced OER performance than the single ligand‐derived counterpart resulting from the cooperated electronic interaction between the two organic linkers with different electron‐donating group .…”
Section: Introductionmentioning
confidence: 79%
“…It was found that various factors including the feed ratio of the reactant components, preparation process, condition control, and characterization method have been found to be significantly regulated the morphologies and electronic structures of the resulting electrocatalysts. In particular, the cooperated effects from different components, such as mixed metallic species, structurally related organic ligand as well as the nanomaterials and the substrate, can greatly improve the electrocatalytic performances by modulating the morphological and electronic structures, which then further enhance the electrocatalytic activity and durability through the optimized absorption energy towards the active species . For example, a bimetallic MOF with mixed terephthalate and 2‐aminoterephthalate ligands directly immobilizated on the NF has exhibited enhanced OER performance than the single ligand‐derived counterpart resulting from the cooperated electronic interaction between the two organic linkers with different electron‐donating group .…”
Section: Introductionmentioning
confidence: 79%
“…Mu and coworkers extended this concept by preparing a new type of HE-MOFs with 1,4-benzendicarboxylic acid (1,4-BDC) as ligand by the solution phase method at room temperature ( Figure 3e). [16] The HE-MOFs showed an ultrathin nanosheet structure and Mn 2þ , Fe 3þ , Co 2þ , Ni 2þ , and Cu 2þ are uniformly dispersed on the nanosheets with near-equimolar ratios according to the results of energy dispersive spectrometer Figure 3. a) Metal elements precisely accumulated on the phenylazomethine (DPA) dendrimer (purple-colored) and concept of the "atom hybridization" method.…”
Section: High-entropy Mofsmentioning
confidence: 96%
“…Mu and coworkers extended this concept by preparing a new type of HE‐MOFs with 1,4‐benzendicarboxylic acid (1,4‐BDC) as ligand by the solution phase method at room temperature (Figure 3e). [ 16 ] The HE‐MOFs showed an ultrathin nanosheet structure and Mn 2+ , Fe 3+ , Co 2+ , Ni 2+ , and Cu 2+ are uniformly dispersed on the nanosheets with near‐equimolar ratios according to the results of energy dispersive spectrometer (EDS) mapping (Figure 3f) and ICP characterization. In contrast, HE‐MOFs could not form under solvothermal reaction conditions applied for traditional MOFs containing bimetallic or trimetallic metals, mainly due to the poor mass transfer.…”
Section: Synthesis Strategies Of Hem‐npsmentioning
confidence: 99%
See 2 more Smart Citations